The Effect of STEM Integrated Project Based Learning Model on Students' Critical Thinking Ability in Geography Subjects - Dwi Raudatul Jannah; Alfi Sahrina; Dwiyono Hari Utomo (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
Critical thinking ability is a 21st-century skill that is still lacking well empowerment. Efforts that can be made to improve These skills are through student-centred learning. Model STEM-integrated Project Based Learning encourages contextual learning through project activities. Indirectly, this builds thinking skills critical students in each syntax. This study aims to identify the effect of the model STEM-integrated Project Based Learning on student's critical thinking skills in geography subjects. This research uses a quasi-experimental research type by applying the Post-test Only Control Group Design. The research subject is students of class X IPS 7 and X IPS 9 MAN Bondowoso. The instrument used is a test essay. Data analysis using Independent Samples - Obtain test information p - level 0.00 <0.05 with a mean post-test score of the experimental class 82, and control class 70. It is concluded that the STEM-integrated Project Based Learning model has a significant effect on critical thinking skills.